Arrangement Of Text-Based Handbooks To Enhance Writing Skills In Arabic Language Education - Maimuna Maimuna; Muhammad Ainin; R Taufiqurrahman (Ijaz Arabi Journal of Arabic Learning, 2022)
This research aims to produce text-based handbooks and To describe the feasibility of handbooks validation. The research employs an RD (Research and Development) design by developing the Addie research model. For the data collection technique, the researcher uses the method of observation, interviews, questionnaires and examinations. Researchers used pretest and posttest trials to try out the product effectiveness. The results of the study claim: 1. The process of developing teaching materials with a Genre Based Pedagogy Approach, namely this book contains introduction, guidelines for using the book, indicators of achievement, then this book consists of 4 stages. Building Knowledge of The Field, Modeling, Joint Contruction, Independent contruction. 2. The results of expert validation: (a) Content and content expert, the resulting percentage is 88%, b). The linguist, the resulting percentage is 56.7%, (c). The design expert, the resulting percentage is 75%. Then based on content and content experts, language and design, the percentage produced at the “excellent” level. 3. Effective use of teaching materials with Genre Based Pedagogy Approach: comparison between pretest and posttest with t test analysis. The conclusion is the use of teaching materials with the Genre Based Pedagogy Approach is effective for improving writing skills in Arabic language education at the Islamic University of Malang. Individual significant (uji t) test results show that probabilitas (p) = 0.000, t-hitung= 9.605 dan t-tabel=2.47863. Than score p 0.05 and nilai t-hitung t-tabel is Significant influence on the product tested by researchers, namely the product is able to improve writing skills in islamic universities unfortunately so that the hypothesis that the researcher proposes is accepted. The formal finding of this research is “the arrangement of text-based handbooks can make study writing skills